Reviewer Acknowledgements - Lee, Jean (Business Management and Strategy, 2021)
Business Management and Strategy (BMS) would like to acknowledge the following reviewers for their assistance with peer review of manuscripts for this issue. Many authors, regardless of whether BMS publishes their work, appreciate the helpful feedback provided by the reviewers. Their comments and suggestions were of great help to the authors in improving the quality of their papers. Each of the reviewers listed below returned at least one review for this issue. Reviewers for Volume 12, Number 2 Agha Usama Hasan, University of West London, UK Eddie John Paul Fisher, Universidad de Oriente, UK Halimahton Borhan, Universiti Teknologi Mara, Malaysia Izabella Manukyan, Russian-Armenian University, Armenia Jawon Kim, Chung-Ang University, Korea Prince Ewudzie Quansah, Jiangsu University, Ghana Shalini Sahni, Banarsidas Chandiwala Institute of Professional Studies, India Soolakshna Lukea Bhiwajee, University Of Technology, Mauritius, Mauritius Sulaiman Sheik Abdullah, Pasumpon Muthuramalinga Thevar College, India Zheng Xu, Monash University, Australia Jean Lee Business Management and Strategy Macrothink Institute ************************************* Add: 5348 Vegas Dr.#825 Las Vegas, Nevada 89108 United States Tel: 1-702-953-1852 ext.508 E-mail1: bms@macrothink.org E-mail2: bms@macrothink.com Website: http://bms.macrothink.org